Pengaruh Media Leaflet Terhadap Pengetahuan dan Sikap Siswa Tentang Kekerasan dalam Pacaran pada Siswa SMK Satya Bhakti Tahun 2023 - Halmawati, Leni (Journal of Midwifery and Public Health, 2023)
Dating violence, acts of violence against premarital couples, have a significant impact on the victim's life journey. Previous studies have shown that women who are victims of physical or sexual violence in dating are at risk of experiencing more health complaints. This study aims to evaluate the influence of leaflet media on the knowledge and attitudes of SMK Satya Bhakti students in 2023 regarding dating violence. The research method uses a Quasi-Experimental design with a Group Pretest-Posttest approach. The sample involved 36 students from the population of SMK Satya Bhakti Tasikmalaya. The results showed significant differences in students' knowledge and attitudes after receiving education using leaflet media (P value knowledge: 0.000, P value attitude: 0.000). Students need to improve their knowledge by searching for clear information on the internet or participating in health education activities to reject violent dating behavior and prevent risks that may arise.